EFEKTIVITAS TEKNIK RELAKSASI NAPAS DALAM KOMBINASI GUIDED IMAGERY DENGAN MUSIK TERHADAP SKALA NYERI PADA PASIEN POST OPERASI FRAKTUR DI RS. SITI KHODIJAH SEPANJANG - Ira Purnamasari; Dede Nasrullah; Mundakir Mundakir; Uswatun Hasanah; Idham Choliq (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Fracture is bone damage caused by trauma, namely excessive pressure on the bone, surgery is one of the fracture management, the problem that often arises in postoperative fracture patients is pain. Pain is an uncomfortable or unpleasant symptom caused by tissue damage. Deep breathing relaxation and guided imagery are non-pharmacological techniques to reduce pain. The aimed of this research was to determine the effect of giving deep breathing relaxation techniques combination with guided imagery with music on pain scale in postoperative fracture patients at the Siti Khodijah hospital.Methods: This article used pre-experimental with one group pre-test post-test design. The sampling techniques was purposive sampling where a sample of 20 respondents was obtained. The data analysis techniques used a paired sample t- test program with a significance level of α=0.05.Results: showed that the deep breathing relaxation technique combination with guided imagery with music proved to be effective in reducing pain scale in postoperative extremity fracture patients at the Siti Khodijah hospital. The pain scale before the intervention was moderate pain (70%) and severe pain (30%), while the pain scale after the intervention was mild pain (45%) and moderate pain (55%) (p value=0.000 < α=0.05), then H1 is accepted and H0 is rejected.Conclusion: deep breathing relaxation techniques combination with guided imagery with music can reduce pain intensity in postoperative fracture patients at the Siti Khodijah hospital. The application of these techniques can be carried out according to SOP so that nurses do not only focus on pharmacological treatment.